CD11c participates in triggering acute graft‐versus‐host disease during bone marrow transplantation. Issue 1 (2nd June 2021) - Wang, Qianqian; Su, Xiuhua; He, Yi; Wang, Mei; Yang, Donglin; Zhang, Rongli; Wei, Jialin; Ma, Qiaoling; Zhai, Weihua; Pang, Aiming; Huang, Yong; Feng, Sizhou; et al.
Abstract: CD11c is a canonical dendritic cell (DC) marker with poorly defined functions in the immune system. Here, we found that blocking CD11c on human peripheral blood mononuclear cell‐derived DCs (MoDCs) inhibited the proliferation of CD4 + T cells and the differentiation into IFN‐γ‐producing T helper 1 (Th1) cells, which were critical in acute graft‐versus‐host disease (aGVHD) pathogenesis. Using allogeneic bone marrow transplantation (allo‐BMT) murine models, we consistently found that CD11c‐deficient recipient mice had alleviated aGVHD symptoms for the decreased IFN‐γ‐expressing CD4 + Th1 cells and CD8 + T cells. Transcriptional analysis showed that CD11c participated in several immune regulation functions including maintaining antigen presentation of APCs. CD11c‐deficient bone marrow‐derived DCs (BMDCs) impaired the antigen presentation function in coculture assay. Mechanistically, CD11c interacted with MHCII and Hsp90 and participated in the phosphorylation of Akt and Erk1/2 in DCs after multiple inflammatory stimulations. Therefore, CD11c played crucial roles in triggering aGVHD and might serve as a potential target for the prevention and treatment of aGVHD. Abstract : CD11c‐deficient recipient mice had alleviated aGVHD symptoms for the decreased IFN‐γ‐expressing CD4 + Th1 cells and CD8 + T cells during mice allo‐BMT. CD11c participated in triggering aGVHD and maintaining antigen presentation function of APCs. Mechanistically, CD11c interacted with MHCII and Hsp90 and participated in the phosphorylation of Akt and Erk1/2 in DCs after multiple inflammatory stimulations.